2023
DOI: 10.3389/fonc.2023.1155123
|View full text |Cite
|
Sign up to set email alerts
|

Association between inflammatory bowel disease and pancreatic cancer: results from the two-sample Mendelian randomization study

Yu Min,
Zheran Liu,
Ruidan Li
et al.

Abstract: BackgroundThe nuanced relationship between inflammatory bowel disease (IBD) and pancreatic cancer is noticed in recent years. However, the underlying causal effects of these two diseases are still unclear.MethodsThe two-sample mendelian randomization (MR) was conducted to explore the causal effect of IBD condition on pancreatic cancer. Methods of Wald ratio, inverse variance weighted (IVW), MR-Egger, weighted median, and weighted mode were used to investigate the causal relationship between IBD and pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Lastly, genetic factors that predispose individuals to IBD might also be linked to an increased risk of pancreatic cancer 36,37 . Our study revealed that IBD is associated with a raised risk of pancreatic cancer based on MR studies 28,29 . Exacerbating inflammation in the pancreas caused by shared genetic factors may contribute to the development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Lastly, genetic factors that predispose individuals to IBD might also be linked to an increased risk of pancreatic cancer 36,37 . Our study revealed that IBD is associated with a raised risk of pancreatic cancer based on MR studies 28,29 . Exacerbating inflammation in the pancreas caused by shared genetic factors may contribute to the development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 64%
“…According to the study by Huang et al., 28 the results of the IVW estimates demonstrated that genetic liability to IBD was associated with an increased risk of pancreatic cancer development (odds ratio [OR] = 1.18 [95% CI: 1.04–1.34]). The MR study by Min et al 29 . also showed that patients with a genetic predisposition to IBD, especially CD, are at an increased risk of developing pancreatic cancer.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…During analyses of causal effects between CD and extraintestinal cancers, we discovered that the incidence of pancreatic cancer in patients with CD is 1.10 times higher in the European population and 1.19 times higher in the East Asian population compared to individuals without CD. Similarly, Yu's MR study showed a causal effect between CD and pancreatic cancer risk (OR: 1.111; 95% CI: 1.015-1.213) in Europeans (47). Two studies, one involving Scandinavians and the other Koreans, also consistently reported that CD increases the risk of pancreatic cancer (48, 49).…”
Section: Discussionmentioning
confidence: 88%